Sweat Testing and Recent Advances - Yasemin Gokdemir; Bulent Taner Karadag (Frontiers Media S.A., 2021)
Cystic fibrosis (CF) is the most common fatal genetic disease of the Caucasian population. Sweat testing is the principal diagnostic test for CF, and it is used for the evaluation of infants with positive CF newborn screening (NBS) and in patients with clinical findings suggesting CF. This article describes the classical sweat test method in detail and also provides an overwiew of recent advances.